Blockade of B7-H1 (Programmed Death Ligand 1) Enhances Humoral Immunity by Positively Regulating the Generation of T Follicular Helper Cells - FALLON, PADRAIC; HAMS, EMILY; AMU, SYLVIE (My University, 2011)
T follicular helper (TFH) cells are critical initiators in the development of T cell-dependent humoral immunity and the generation of protective immunity. We demonstrate that TFH cell accumulation and Ab production are negatively regulated by B7-H1 (programmed death ligand 1) in response to both helminth infection and active immunization. Following immunization of B7-H1?/? mice with keyhole limpet hemocyanin or helminth Ags, there is a profound increase in induction of TFH cells as a result of increased cell cycling and decreased apoptosis relative to wild-type mice. The increase in TFH cells in the absence of B7-H1 was associated with significant elevations in Ag-specific Ig response. Cotransfer experiments in vivo demonstrated that B7-H1 expression on B cells was required for negatively regulating TFH cell expansion and production of Ag-specific Ig. Treatment of immunized wild-type mice with anti?B7-H1 or anti-programmed death 1 mAbs, but not anti?B7-DC, led to a significant expansion of the TFH cell population and an enhanced Ag-specific Ig response. Our results demonstrate that the coinhibitory B7-H1/programmed death 1 pathway can limit the expansion of TFH cells and constrain Ag-specific Ig responses. This finding has direct implications for investigations examining the feasibility of therapeutically manipulating this pathway and reveals new insights into the regulation of the humoral immune response.
PUBLISHED
Keywords: Immunology; TFH cells; Immunology, Inflammation & Infection